Hepatoprotective activity of fruit extract of Garcinia pedunculata - Ravi Mundugaru; Madhan Chakkravarthy; Ravishankar Basavaiah (Bangladesh Pharmacological Society, 2014)
The objective of this study was to explore the hepatoprotective activity of fruits of Garcinia pedunculata in paracetamol-induced liver toxicity in rats. Paracetamol-induced hepatotoxicity was evaluated by an increase in serum transaminases and alkaline phosphatase activity. Histopathological observation showed extensive disturbance in the liver cytoarchitecture in comparison to normal control liver sections. Pre-treatment with aqueous extract of fruits of G. pedunculata prevented the paracetamol-induced increase in serum transaminases, alkaline phosphatase and histopathological changes. Based on the above observation it can be concluded that G. pedunculata pretreatment exhibited significant hepatoprotective activity against paracetamol-induced hepatotoxicity.